Analisis Penyelesaian Kredit Macet Berdasarkan Konsep Menyama Braya Di Bumdesa Pandan Harum Selat - Kadek Eni Andriani; I Gede Agus Pertama Yudantara (Universitas Pendidikan Ganesha, 2021)
This study aims to determine the factors that cause bad credit in Pandan Harum BUMDesa Selat Village and to find out how to solve the bad credit in Pandan Harum BUMDesa Selat Village based on the concept of nyama braya. This research was conducted at BUMDesa Pandan Harum, Selat Village, Sukasada District, Buleleng Regency, Bali. This study used qualitative research methods. Data collection in this study was carried out through interviews conducted with the Chairman of BUMDesa Pandan Harum Selat, the Secretary, the Selat Village Headquarters, and customers, the second was observation, and the last was documentation. The data analysis technique used in this research is data reduction, data presentation, data analysis and conclusion drawing. The results of this study indicate that there are 3 factors that cause credit, namely weak internal control in procedures for granting and returning credit, lack of public awareness, and the state of the community's economy. To solve the problem of bad credit, the concept of nyama braya was applied, namely by updating the internal control system, approaching the community based on the concept of nyama braya, and forming the